Rethinking scientific literacy - Roth, Wolff-Michael (RoutledgeFalmer/Taylor & Francis Group, 2004)
The authors propose a complete rethinking of scientific literacy consistent with lines of thought in cultural studies, cultural sociology, and particularly concepts that come from neo-Marxist scholarship